Production of biodiesel from palm oil using alumina supported potassium iodide catalyst with nickel dopant / Shahida Hanum Kamarullah...[et al.] - Kamarullah, Shahida Hanum; Abdul Razak, Zainal Kifli; Mohd Shohaimi, Norshahidatul Akmar; Zuply, Khairina Farhana; Azri, Nur Syafika (Universiti Teknologi MARA Cawangan Pahang, 2019)
Biodiesel is eco-friendly and proven to be environmentally safe compared to the conventional diesel fuel. Transesterification is the common technique used for biodiesel production in order to reduce the viscosity of triglycerides. In this study, biodiesel was produced by transesterification of palm oil utilizing potassium iodide (KI) supported on alumina beads catalyst with nickel as a dopant. The objective of this study is to investigate the effects of nickel as dopant towards the transesterification reactions. The reactions were refluxed at 65°C with 5 hours reaction time while varying the catalyst loading (0 wt%-8 wt%) and methanol to oil molar ratio at (1:15-1:55). Theoptimum methanol to oil ratio was 1:35 and 4 wt%catalyst loading produced FAME yield of53.34%. Thermogravimetric analysis (TGA) results proved that the catalyst has undergone two stages of decomposition with 23.47% total weight loss. GCMS results showed six peaks of methyl esters which reveal that nickel that act as dopant has greatly affected the reactivity of the catalyst